The effect of hydrothermal conditions on surface properties of synthesized nano SBA-15 using sodium silicate - Kareem, Yousra S.; Hussein, Hussein Q.; Abdul-Majeed, Wameath S. (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
A successful synthesis of mesoporous Santa Barbara amorphous (SBA-15) with nanoparticle size was attempted using prepared sodium silicate from Iraqi high silica sand. EO20PO70EO20 copolymer was used as a template at highly acidic conditions (pH < 2). The effect of crystallization temperature of (100, 110, 120, and 130 0C), and crystallization time of (24, 48, 72, and 120 h) on surface properties was studied. The experiments were characterized using XRD, FTIR, AFM, BET, and FESEM. The XRD and FTIR tests represent amorphous SBA-15 without any impurities. Decreasing average particle size distribution increased the surface area, and decreased the porosity (pore volume, and pore size) in all experiments. The texture properties were surface area of 210-756 cm2/g, volume pore of 0.28-0.7 cm3/g, and pore size of 1.94-13.45 nm. The optimum result of surface area was achieved at hydrothermal conditions of 110 0C, and 24 h, while optimum results of pore volume, and pore size were achieved at hydrothermal conditions of 100 0C, and 120 h. Semi-spherical shape of particles appeared at hydrothermal conditions of 120 0C and 24 h. This morphology was transferred to small rods at 130 0C, and to semi-platelets at 120 h.